A Review of the Relationship between Wine Consumption and Type 2 Diabetes Mellitus - Stockley, Creina S. (Journal of Nutritional Therapeutics, 2016)
The potential health benefits of moderate alcohol consumption are not limited to a reduced risk of cardiovascular disease but are also observed for type 2 diabetes mellitus. The relationship appears to be J-shaped where moderate alcohol consumption reduces the risk of developing type 2 diabetes mellitus in both men and women, irrespective of age, and in those with a low and a high body mass index. The optimal amount of wine appears to be approximately two drinks per day, where a standard drink in Australia is considered to be 10 g alcohol. Given that the incidence of diabetes is projected to approximately double in the next 15 years, simple dietary supplementation to a healthy diet and lifestyle to reduce the risk will become increasingly important. This paper reviews the association between wine specifically and type 2 diabetes mellitus, and discusses biological mechanisms related to the association